THOUGHT PATTERNS UNDERLYING THE JAKARTA POST’S SPECIFIC FEATURES: DO THEY REFLECT THE ENGLISH CULTURE? - Katharina Rustipa (Dinamika Bahasa dan Budaya, 2010)
A language user employs a particular thought pattern to express ideas.  The author, using his or her language, knowledge, thought, experience and world-view, expresses his ideas or intention in the written text. On the other hand, the reader, using his or her knowledge, language, thought, and  his or her view of the world, attempts to reconstruct  or interpret what the author  has expressed  in the written text. Because of the obvious difference between the writer’s world view and the reader’s world view, perfect comprehension can never be achieved.  So, communication problems sometimes arise, particularly when they (the reader and the writer) come from different cultural backgrounds. The purpose of  this study is  investigating the thought patterns that underlie the writing of The Jakarta Post’s English specific features performed by ‘matured’ Indonesians. The research design of the study is as follows: 1) selecting English specific features written by Indonesians, 2) observing the profiles of every text by identifying the title, the thesis statement, the topic sentences, the relation of ideas between paragraphs (thesis statement and topic sentences) and within paragraph (between the topic sentence and supporting sentences), pattern of development. The research results show  that the thought pattern underlying the English specific features written by Indonesians in The Jakarta Post is linear. The values characterize the manifestation of the thought patterns underlying the English specific features written by Indonesians are: usefulness, practicality, workable. It is suggested that 1) the language learners should be familiar with the thought pattern of the target language, 2) Language learners should be exposed with the target language because the exposure to the targetlanguage may influence their thought pattern or way of thinking when writing the texts of the target language. Key words: thought pattern, linear, non linear, deductive, inductive, digression, direct, indirect, coherent, incoherent